A New Approach to Operations on Neutrosophic Soft Sets and to Neutrosophic Soft Topological Spaces - Ozturk, Taha Yasin; Gunduz Aras, Cigdem; Bayramov, Sadi (Communications in Mathematics and Applications, 2019)
In this study, we re-define some operations on neutrosophic soft sets differently from the studies [3, 9]. On this operations are given interesting examples and them basic properties. In the direction of these newly defined operations, we construct the neutrosophic soft topological spaces differently from the study [3]. Finally, we introduce basic definitions and theorems on neutrosophic soft topological spaces.